Flame-retardant polyesters. II. Polyester polymers - Yang, Seung-Cheol; Kim, Jae Pil (Journal of applied polymer science, 2007)
Two flame‐retardant polyesters were polymerized with two types of phosphorous flame retardants. 3‐(Hydroxyphenyl phosphinyl)propanoic acid (HPP) was used as a main‐chain type, and 9,10‐dihydro‐9‐oxa‐10‐2,3‐dicarbonylpropyl‐10‐phosphophenanthrene‐10‐oxide (DI) was used as a pendant type. Polymerization was accomplished on a commercial scale with a three‐reactor system to exclude the compositional variation of oligomeric ethylene terephthalate. A longer polycondensation time and a higher dosage of the catalyst were necessary for DI with respect to HPP because of the high content and relatively low reactivity of the flame retardant. However, the content of diethylene glycol (DEG) in the polyester, which formed during the polymerization, was much higher in the case of HPP. The produced polyesters had almost the same molecular weight, but the DEG contents in the polyesters were quite different. The higher DEG content in the HPP polyester reduced the thermal stability. The greater flexibility of the HPP polyester chain resulted in easier crystallization and a lower crystalline temperature. The HPP polyester had higher susceptibility to thermal degradation because of low resistance to thermal chain scission, degraded at a lower temperature, and was more easily degraded because of a weak PO bond linkage in the main chain. The DI polyester, whose phosphorous atom was highly sterically hindered, showed better alkaline resistance than the HPP polyester because of the lower acidity and lower hydrophilic DEG content. © 2007 Wiley Periodicals, Inc. J Appl Polym Sci 2007